Where is Territorial Peace? Violence, Drug Trafficking and Territory: The Killings of Former Guerrilla Combatants and Social Leaders in Colombia (2016-2021) - Ríos, Jerónimo (PARTECIPAZIONE E CONFLITTO, 2022)
The aim of this study is to analyse the phenomenon of the killings of former FARC-EP guerrilla fighters and social leaders committed in Colombia between November 2016, when the Peace Agreement was signed, and June 2021. It argues for the need to focus the analysis on nine departments, which account for most of this type of violent homicide. This violence is closely linked to armed groups, both in the form of FARC-EP guerrillas and dissidents, as well as post-paramilitary and other criminal groups that fuel the armed conflict. This forms part of the continuation of the geography of violence that existed before the Peace Agreement, albeit with new armed actors following the demobilisation of the guerrillas. One factor explaining the violence is the drug trafficking industry, which attracts armed groups that compete for the control of resources and find in former FARC-EP combatants and social leaders people opposed to their illicit interests. Using different correlational exercises, we also note the need for future research to shed light on a phenomenon that has so far been little studied, and which highlights the limited capacity for transforming the violence that, for the time being, accompanies the Peace Agreement signed in 2016.